Upaya Kepala Sekolah dalam Meningkatkan Kinerja Guru SMK Negeri 1 Simpang Teritip - Hasdiah Hasdiah (LPPM STIE PERTIBA Pangkalpinang, 2019)
Decentralization of education raises the importance of a leader, the principal. The principal plays a very important role in managing the school's resources and carrying out its duties and authority which must be carried out properly. For this reason, school principals are required to truly have the ability to be able to carry out these tasks. The principal is the key to success and progress in improving the quality of the school. Based on the discussion, it can be concluded that: 1) the efforts made by school principals in improving teacher performance, namely: a) involving teachers in education and training; b) provide the facilities needed in the learning process; c) encourage/remind teachers to utilize the facilities that have been provided; d) gives the teacher freedom in the use of learning methods; e) provides attendance and checking periodically; f) setting the teacher's desk to facilitate communication; g) supervise every learning activity; h) provide motivation, direction and examples to the teacher; i) give a warning to teachers who lack discipline, and j) the principal is open and provides an example to the teacher. 2) These efforts can be said to be effective in improving teacher performance because teacher performance is better and orderly starting from planning, implementing learning to evaluating/evaluating learning